2008
DOI: 10.1128/aac.01297-07
|View full text |Cite
|
Sign up to set email alerts
|

Potent In Vitro Antifungal Activities of Naturally Occurring Acetylenic Acids

Abstract: Our continuing effort in antifungal natural product discovery has led to the identification of five 6-acetylenic acids with chain lengths from C 16 to C 20 : 6-hexadecynoic acid (compound 1), 6-heptadecynoic acid (compound 2), 6-octadecynoic acid (compound 3), 6-nonadecynoic acid (compound 4), and 6-icosynoic acid (compound 5) from the plant Sommera sabiceoides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
85
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 33 publications
1
85
0
Order By: Relevance
“…They have been reported to possess a diversity of pharmacological properties, including antibacterial, antifungal, antiparasitic, and antitumor activities (reviewed in references 6 and 44). We have previously described the antifungal properties of 6-acetylenic acids (triple bond at C-6) that were isolated from the plants Pentagonia gigantifolia and Sommera sabiceoides (21,22). Among these, 6-nonadecyonic acid (6-NDA), with a chain length of C 19 (see the structure shown in Fig.…”
mentioning
confidence: 99%
“…They have been reported to possess a diversity of pharmacological properties, including antibacterial, antifungal, antiparasitic, and antitumor activities (reviewed in references 6 and 44). We have previously described the antifungal properties of 6-acetylenic acids (triple bond at C-6) that were isolated from the plants Pentagonia gigantifolia and Sommera sabiceoides (21,22). Among these, 6-nonadecyonic acid (6-NDA), with a chain length of C 19 (see the structure shown in Fig.…”
mentioning
confidence: 99%
“…While phytosterols are known to have bioactive prevention properties such as lowering of cholesterol levels [44] and cancer prevention [45] properties. Previous research by Li et al [46] showed that unsaturated fatty acids have antifungal potencies, low toxicities and good pharmaceutical properties.…”
Section: Phytochemistrymentioning
confidence: 99%
“…Many polyacetylenics have highly potent biological activities, which are used in defence against pathogens and predators 3,12,15 , and some have been investigated as human anti-cancer and anti-microbial treatments 13,16,18,20 . Conjugated polyacetylenic compounds are also very difficult to synthesize chemically; however, we have described a biosynthetic route using soldier beetle genes for heterologous production of these chemicals in yeast using mild conditions.…”
Section: Figure 5 | Phylogenetic Analysis Of Insect Desaturasesmentioning
confidence: 99%
“…The challenging chemistry and variety of potent biological activities of polyacetylenic fatty acids, which includes activities against cancer cells, infecting microbes and plant alleopathy [12][13][14][15][16][17][18][19][20] , have excited interest among natural-product prospectors and bioactive discovery programmes, and have propelled our interest in new molecular structures and biosynthetic origins. In this report, we describe a three-gene pathway isolated from the Australian soldier beetle C. lugubris, leading to an 18-carbon precursor of DHMA, and the first eukaryote biosynthesis of conjugated polyacetylenic compounds.…”
mentioning
confidence: 99%